Analysis The Influence of Management Implementation Strategic For The Quality Islamic Education at Madrasah Ibtidaiyah Al-Istiqomah Telagawaru - Ahmad, Ramli; Wahyudiati, Dwi; Citriadin, Yudin (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
This research aims to show the significant influence of the application of strategic management on the nature of Islam at Madrasah Al-Istiqomah Telagawaru which is located in Labuapi District, West Lombok Regency. The research used is an quantitative method approach with data analysis techniques using an analytical design. The research is all teachers and students of MI Al-Istiqomah Telagawaru, and the sample consists of eight teachers and six eleven students who were randomly selected. The data collection method is through observation, using instruments to assess the implementation of management and Islamic education. The data analysis technique used is the t test and/or F test. So the results of the research show that the influence of the application of strategic management has a significant influence on the quality of Islamic education in the MI in Al-Istiqomah Telagawaru, with the significant value obtained in the T test and the F test amounting to I0.000, which is less than 0.05. Therefore, we confidently reject Ho and accept Ha.